Možnosti kemične predelave bukovega lesa - Zule, Janja (Gozdarski vestnik, 2015)
This article presents chemical composition of beech wood as well as various possibilities for its chemical conversion. The useful components of beech biomass are primarily cellulose fibers, xylan and lignin. Some of the most important technological procedures for wood fractionation are described, as for example hydrolysis, fermentation, pyrolysis and extraction, together with marketable products which are produced in the processes. The greatest potential for the future is ascribed to the production of nanofibrilated cellulose, which is considered to become the raw material of the future. Recent research has indicated that beech wood and bark contain high added value bioactive compounds, while seeds are extremely reach source of high quality oil. Beech wood, including waste such as bark and sawdust, represent reach raw material which might be conveniently converted to different marketable products.
Keywords: bukov les; frakcioniranje biomase; celulozna vlakna; ksilan; lignin; nanofibrilirana celuloza; kemična predelava; dodana vrednost